Exoplanet plenitude - Martín, E.L. (Advances in Astronomy and Space Physics, 2012)
The main aim of the present paper is to give a brief overview of the revolution in exoplanet discoveries which started about two decades ago and the new concepts and perspectives that these observational findings have brought about. The level of the text is simple, as deemed suitable for reading by young scientists with different levels of expertise. The paper is organized in the following sections: 1) Historical background. 2) Basic concepts and definitions of what is a planet. 3) Observational evidence of planetary diversity and the theoretical pathways to explain what we see. 4) Future research directions.